From Plant Survival Under Severe Stress to Anti-Viral Human Defense – A Perspective That Calls for Common Efforts - Arnholdt-Schmitt, Birgit; Mohanapriya, Gunasekaran; Bharadwaj, Revuru; Noceda, Carlos; Macedo, Elisete Santos; Sathishkumar, Ramalingam; Gupta, Kapuganti Jagadis; Sircar, Debabrata; Kumar, Sarma Rajeev; Srivastava, Shivani; Adholeya, Alok; Thiers, KarineLeitão Lima; et al. (Frontiers in Immunology, 2021)
Reprogramming of primary virus-infected cells is the critical step that turns viral attacks harmful to humans by initiating super-spreading at cell, organism and population levels. To develop early anti-viral therapies and proactive administration, it is important to understand the very first steps of this process. Plant somatic embryogenesis (SE) is the earliest and most studied model for de novo programming upon severe stress that, in contrast to virus attacks, promotes individual cell and organism survival. We argue that transcript level profiles of justified target genes established from in vitro SE induction as reference compared to virus-induced profiles can identify differential virus traits that link to harmful reprogramming. In this perspective, we highlight relevant background knowledge on SE and emphasize the role of alternative oxidase in plant resilience/robustness as a learning tool for designing human virus-defense strategies. Further, we propose ‘ReprogVirus’ as a standard gene profile tool to identify critical virus-specific and virus–unspecific early footprints as targets for designing anti-viral strategies. Genes were selected by considering (a) state-of-the-art molecular characteristics of ‘reprogramming for survival’ during SE induction raised in the background and, (b) by recognizing that viruses, by structural violence, ‘abuse’ these same tools for host reprogramming/manipulation to favor their own replication. In a parallel research, this interdisciplinary approach resulted in identifying ‘CoV-MAC-TED’, a complex trait that is promising to support combating SARS-CoV-2-induced cell reprogramming in primary infected nose and mouth cells. Here, we initiate wider data collection in a ‘ReprogVirus Platform’ to support anti-viral strategy design through common efforts.